A Study on Occupational Stress among University Librarians in India: Understanding the Impact of Technological Changes on Occupational Stress among University Librarians in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Stress is a universal element which faces us in every way of life and which has both positive and negative implications for employees and organizations. Work stress is also referred to as burnout. Burnout is an expression of physiology and a wellness sense. This is also seen as a feeling of imbalance at the same time. Furthermore, in different situations it is the way of reacting physically, mentally and emotionally, and cannot be controlled. Stress is also like wrath, frustration, anguish, tension and depression in a burnout, where the person feels bad emotions. In today's world, librarian professionals appear to suffer from occupational stress due to changing technological conditions and the needs for information. A structured questionnaire was built in two parts the general data sheet and occupational stress for collecting primary data, which were distributed among the 100 professional librarians randomly selected as a sample. The purpose of this paper is to learn how stressful librarians are in India.